Investment and Environmental Impact Assestment: Impact of the Change in Environmental Approval Regulations towards Environmental Sustainability under the Job Creation Act - Syafrinaldi, Rani Fadhila (The Opole Studies in Administration and Law, 2024)
The abolition of environmental permits for business activities in the Ciptaker Law has generated quite reasonable debate. Environmental permits are one method of preventing environmental damage and pollution. The abolition of this environmental permit aims to facilitate investment for investors, both domestic and foreign investors. This article will discuss the function of licensing and what are the impacts and threats to the environment of the abolition of environmental permits in the Ciptaker Law.